Could Hormone Levels Impact the Severity of Clitoral Phimosis?. (1st August 2022) - Romanello, J; Myers, M; Nico, E; Sussman, R; Marantidis, J; Rubin, R
ABSTRACT: Introduction: Clitoral adhesions (CA) occur when the prepuce adheres to the glans clitoris. CA can be classified as mild, moderate, or severe, based on if more than 75%, 25% to 75%, or less than 25% of the glans clitoris is exposed. Symptoms of CA include pain, difficulty with arousal, and muted or absent orgasm. There is a paucity of information on how hormone levels may contribute to the formation of CA. We hypothesize that patients with lower levels of free and total testosterone, and higher levels of the blood transport protein sex hormone binding globulin (SHBG) could have more severe adhesions. Higher free and total testosterone can yield more oily skin, which may break up or prevent adhesions. Additionally, with higher SHBG, there is less free testosterone available to be used by tissues in the body. Objective: To determine if patients with lower free and total testosterone, and higher SHBG have more severe adhesions. Methods: Charts of females with CA who underwent the non-surgical lysis procedure at one sexual medicine practice were considered for this study. 24 charts contained information on the severity of phimosis before lysis, total and free testosterone levels, as well as SHBG levels around the time of lysis. The study group consisted of patients with mild (n=9), moderate (n=8), or severe (n=7) CA. Results: The average calculated free testosterone among patients with mild, moderate, and severe CA was 0.23ng/dL, 0.35ng/dL, and 0.14ng/dL. The average total testosterone among patients with mild, moderate, and severe CA was 24.79ng/dL, 27.81ng/dL, and 20.26ng/dL. The average SHBG among patients with mild, moderate, and severe CA was 98.69nmol/L, 95.76nmol/L, and 109.40nmol/L. Conclusions: We predicted that patients with more severe adhesions would have lower levels of free and total testosterone, as well as higher levels of SHBG, yet this trend did not appear overall in this data among patients with mild, moderate, or severe adhesions. Additional studies with larger sample sizes are needed to explore the potential impact of free and total testosterone, as well as SHBG levels on the development and severity of CA. Studies could also compare levels of these hormones in patients with and without adhesions, or consider patients with recurrence of adhesions. Insight into a hormonal etiology could be important to patients with altered levels of these hormones - for example, patients with medical conditions such as PCOS, patients taking medications such as oral contraceptive pills, and menopausal women on oral estrogen (as increased estrogen raises levels of SHBG) could be at an increased risk for developing CA. Further studies could also consider if the clitoides of transgender males on gender-affirming hormone therapy with testosterone have lower incidences of CA. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Sprout (Raleigh, NC), Absorption Pharmaceuticals